1999
DOI: 10.1017/s0890037x00041646
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Sweet Corn (Zea mays) Hybrids to RPA 201772

Abstract: Field studies at Arlington, WI, and LeSueur, MN, were conducted in 1996 and 1997 to evaluate tolerance of six sweet corn hybrids to RPA 201772 applied preemergence at 79 to 210 g/ha. Both years the most sensitive hybrid at the Wisconsin site was ‘Zenith,’ with yield reductions of 14 and 22% at 210 g/ha (twice the labeled rate). ‘Excellency,’ ‘Green Giant 43,’ and ‘Jubilee’ tolerated RPA 201772 at 158 g/ha or less. The least tolerant hybrids in Minnesota were ‘Green Giant 6′ and Jubilee, and the most tolerant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
1
6
0
3
Order By: Relevance
“…Isoxaflutole reduced sweet corn height as much as 12% and 18% in some hybrids when applied at 105 and 210 g a.i./ha, respectively. These reductions are comparable to those measured by O'Sullivan et al (2001) and Van Wychen et al (1999). Isoxaflutole + cyprosulfamide did not reduce sweet corn height at either rate.…”
Section: Plant Heightsupporting
confidence: 80%
See 1 more Smart Citation
“…Isoxaflutole reduced sweet corn height as much as 12% and 18% in some hybrids when applied at 105 and 210 g a.i./ha, respectively. These reductions are comparable to those measured by O'Sullivan et al (2001) and Van Wychen et al (1999). Isoxaflutole + cyprosulfamide did not reduce sweet corn height at either rate.…”
Section: Plant Heightsupporting
confidence: 80%
“…Earlier studies with isoxaflutole have shown unacceptable crop injury in some sweet corn hybrids in Ontario and other geographic areas (O'Sullivan et al, 2001;Van Wychen et al, 1999;Wicks et al, 2007). The manufacturer of isoxaflutole (Bayer Ò Inc.) has recently introduced isoxaflutole in combination with a safener, cyprosulfamide, thus allowing PRE and early POST application through the V2 stage (two leaves with visible leaf collars) of field corn (Owen, 2011).…”
mentioning
confidence: 99%
“…A diferença de seletividade de um mesmo produto em relação a diferentes cultivares já havia sido evidenciada em outras culturas por Damião Filho et al (1996), Land et al (1999), Wychen et al (1999), Wilson (1999), Pereira et al (2000) e Cavalieri et al (2008). Para mandioca, Oliveira Jr.…”
Section: Resultsunclassified
“…Land et al (1999) demonstraram que o índi-ce de resistência de plantas de milho ao trifluralin é uma característica genética e que descendentes oriundos do cruzamento entre dois híbridos resistentes têm tolerância ao herbicida ainda maior que suas progênies. Wychen et al (1999) avaliaram a tolerân-cia de híbridos de milho-doce ao isoxaflutole, concluindo que, além da variabilidade de suscetibilidade inerente aos híbridos, a tolerância variava em função do tipo de solo em que a semeadura era feita. Cavalieri et al (2008), avaliando a seletividade do herbicida nicosulfuron a cinco híbridos de milho, detectaram que um deles apresentou redução significativa de produção.…”
Section: Introductionunclassified
“…Land et al (1999) demonstraram que o índice de resistência de plantas de milho ao trifluralin é uma característica genéti-ca e que descendentes oriundos do cruzamento entre dois híbridos resistentes têm tolerância ao herbicida ainda maior que suas progênies. Wychen et al (1999) avaliaram a tolerância de híbridos de milho doce ao isoxaflutole, concluindo que além da variabilidade de suscetibilidade inerente aos híbridos, a tolerância variava em função do tipo de solo em que o plantio era feito. Wilson (1999) avaliou nove cultivares de beterraba utilizando herbicidas aplicados em pós-emergência e evidenciou que a tolerância variava entre cultivares e até mesmo entre anos de plantio, dentro do mesmo cultivar.…”
Section: Introductionunclassified